Experimental Study on City Road Collapse under Vibrating Load - Yuxiao Wang; Gang Shi; Xiaowei Tian; Chaoyue Li; Huanyu Cheng (Shock and Vibration)
Underground pipeline seepage and traffic load are the important factors causing city road collapse. In this paper, eight groups of indoor scale model experiments are used to study the road collapse caused by pipeline seepage, taking into account the load type, pipeline buried depth, the distance between pipeline and loss channel, the relative position of pipeline and loss channel, and the formation time of loss channel. The results show that when the erosion channel was formed later, the underlying erosion cavity was ellipsoid, while the other erosion cavities were funnel shaped. When only the static load is applied, the time to reach the ultimate failure is longer than that when only dynamic load is applied. The smaller dynamic load can increase the stability of the soil above the seepage pipeline, while the larger dynamic load can accelerate the collapse process. With the formation time of the erosion channel increasing, the erosion void size is larger and the surface is easier to collapse. With the increase of the distance between the loss passage and the pipeline, the damage time of the road surface is also increased. The larger the thickness of the soil layer above the pipeline, the smaller the size of the underground cavity and the surface subsidence.